2019
DOI: 10.1038/s41467-019-11808-3
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy-based single-cell metabolic phenotyping of lung cancer patients for informative diagnostics

Abstract: Accurate prediction of chemo- or targeted therapy responses for patients with similar driver oncogenes through a simple and least-invasive assay represents an unmet need in the clinical diagnosis of non-small cell lung cancer. Using a single-cell on-chip metabolic cytometry and fluorescent metabolic probes, we show metabolic phenotyping on the rare disseminated tumor cells in pleural effusions across a panel of 32 lung adenocarcinoma patients. Our results reveal extensive metabolic heterogeneity of tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 76 publications
1
30
0
Order By: Relevance
“…In addition, several groups have shown that 2-NBDG is useful for monitoring aberrant cellular uptake of d-glucose in tumors in vitro and in vivo [137][138][139][140][141][142][143][144][145]. 2-NBDG has been effectively applied to clinical specimens as well such as biopsy tissues obtained from patients with oral cancer [146,147], esophagus cancer [148], head and neck cancer [149], breast cancer [150], colorectal cancer [151], and for metabolic phenotyping or screening of cancerous cells in pleural effusion or peripheral blood obtained from lung cancer patients [152,153].…”
Section: Uptake Of 2-nbdg Into Mammalian Cells Through Gluts and Its mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several groups have shown that 2-NBDG is useful for monitoring aberrant cellular uptake of d-glucose in tumors in vitro and in vivo [137][138][139][140][141][142][143][144][145]. 2-NBDG has been effectively applied to clinical specimens as well such as biopsy tissues obtained from patients with oral cancer [146,147], esophagus cancer [148], head and neck cancer [149], breast cancer [150], colorectal cancer [151], and for metabolic phenotyping or screening of cancerous cells in pleural effusion or peripheral blood obtained from lung cancer patients [152,153].…”
Section: Uptake Of 2-nbdg Into Mammalian Cells Through Gluts and Its mentioning
confidence: 99%
“…Indeed, successful evaluations of clinical specimens by 2-NBDG have been reported [146][147][148][149][150]. Another possibility is to use 2-NBDG as a marker for metabolic phenotyping of body fluid [152,153,167]. GB2-Cy3 (Em, 555 nm) was synthesized by attaching Cy3, a cyanine dye much smaller than Cy5.5, to C-1 position of d-glucose via a long linker [159] (Figure 4).…”
Section: Development Of D-glucose Analogues That Emit Fluorescence Ofmentioning
confidence: 99%
“…Mass spectrometric analysis of single circulating cancer cells from the blood of patients revealed metabolites that differed among various kinds of cancer cells ( Hiyama et al, 2015 ; Abouleila et al, 2019 ). Fluorescent probes have also been used to characterize metabolism in circulating cancer cells ( Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometric analysis of single circulating cancer cells from the blood of patients revealed metabolites that differed among various kinds of cancer cells (Hiyama et al, 2015. Fluorescent probes have also been used to characterize metabolism in circulating cancer cells (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%